Implementasi K3 dan Pemanfaatan Mesin Pencacah Nilam dalam Meningkatkan Kesejahteraan Petani di Desa Waturempe - Habriani Habriani; Ismiliani Saflia; Rajab Jandipo; La Ode Ichlas Syahrullah Yunus; Panci Yocing; Wa Ode safira Zainab; Zulfan Ramadhan (Jurnal Medika: Medika, 2025)
Occupational Safety and Health (OSH) is a critical aspect of agricultural activities that is often overlooked by farmers, particularly in rural communities. In Waturempe Village, West Muna Regency, most farmers depend on patchouli (Pogostemon cablin) as the primary raw material for essential oil production. However, manual patchouli processing not only results in low productivity and suboptimal yield quality but also exposes farmers to a high risk of workplace accidents. This community service project was designed to: (1) provide education and promote the implementation of OSH among farmers, (2) introduce and train farmers in the use of patchouli chopping machines as an appropriate technology, and (3) enhance farmer welfare by improving efficiency and productivity. The program was carried out through OSH awareness sessions, technical training on machine operation, and field assistance. The outcomes demonstrated an increase in farmers’ knowledge of OSH, improved skills in operating the machines, and up to a 60% increase in chopping efficiency compared to manual methods. Moreover, the more uniform chopping quality contributed to better essential oil quality. Overall, this initiative made a significant contribution to enhancing productivity, income potential, and the welfare of local farmers.